Reconciling Faith and Sufferings: Insights from Sa‘id Ramadhan Al-Buti’s Theodicy - Nurhanisah Senin; Hamidun Mohamad Husin; Nazneen Ismail; Mustafa Kamal Amat Misra; Norsaleha Mohd Salleh (HRMARS, 2024)
Non-Indexed Publication